Layout, conforto e satisfação dos usuários em escritórios: uma avaliação pós-ocupação no edifício da sede administrativa do INPE-CRN - Damore, Aline Dantas de Araújo (2013)
This research aimed to identify the link between the layout of workspaces in offices and the design strategies for environmental comfort. Strategies surveyed were focused on the thermal, visual and luminic comfort. In this research, visual comfort is related to issues of visual integration within and between the interior and exterior of the building. This is a case study conducted at the administrative headquarters of Centro Regional Nordeste do Instituto de Pesquisas Espaciais (INPE-CRN), located in Natal/RN. The methodological strategy used was the Post-Occupancy Evaluation, which combined the survey data on the building (layout of workspaces, bioclimatic strategies adopted in the design, use of these strategies) with some techniques aimed at acquiring qualitative information related to users. The workspace layout is primordial to satisfaction and productivity of workers. Issues such as concentration, communication, privacy, personal identity, density and space efficiency, barriers (access, visual and even ventilation and lighting), among others, are associated with the layout. The environmental comfort is one of the essential elements to maintaining life quality in workplace. Moreover, it is an important factor in user`s perception of the space in which he or she are inserted. Both layout and environmental comfort issues should be collected and analyzed in the establishment phase of the programming step. That way, it is possible to get adequate answers to these questions in subsequent project phases. It was found that changes in the program that occurred over time, especially concerning persons (number and characteristics), resulted in changes in layout, generating high density and inflexible environments. It turns difficult to adjust the furniture to the occupants` requirement, including comfort needs. However, the presence of strategies for environmental quality provides comfort to spaces, ensuring that, even in situations not considered optimal, users perceive the environment in a positive way. It was found that the relationship between environmental comfort and layout takes the following forms: in changing the perception of comfort, depending on the layout of the arrangements; adjustments in layout, due to needs for comfort; and the elevation of user satisfaction and environmental quality due to the presence of strategies comfort even in situations of inadequate layout